2008
DOI: 10.1063/1.2968438
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UV cure on glass structure and fracture properties of nanoporous carbon-doped oxide thin films

Abstract: The effects of UV radiation curing on the glass structure and fracture properties were examined for a class of nanoporous organosilicate low dielectric constant films. A detailed characterization by nuclear magnetic resonance spectroscopy and Fourier transform infrared spectroscopy showed significant changes in the glass structure with increasing curing time, marked by the removal of terminal organic groups and increased network-forming bonds following the initial removal of porogen material. The higher degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…This was experimentally confirmed by Gage and co-authors, who showed that UV cure exposure results in a higher degree of film connectivity in the material and significantly enhances the interfacial adhesion strength, but barely influences the fracture toughness of PECVD carbon-doped oxide films. 36 H. Lin and co-authors 28 and Y. Lin and co-authors 29 demonstrated that the fracture energy of OSG materials, measured under mode-I condition using double-cantilever beam technique, scales linearly with the total number density of the two main networking bonds in an OSG material ( Figure 6). 28 This is because fracture of these materials is a bond breaking process and the energy dissipated during fracture scales with the number of broken networking bonds and with the energy of the bonds.…”
Section: Impact Of Network Structure and Uv Radiation On Mechanical Smentioning
confidence: 99%
“…This was experimentally confirmed by Gage and co-authors, who showed that UV cure exposure results in a higher degree of film connectivity in the material and significantly enhances the interfacial adhesion strength, but barely influences the fracture toughness of PECVD carbon-doped oxide films. 36 H. Lin and co-authors 28 and Y. Lin and co-authors 29 demonstrated that the fracture energy of OSG materials, measured under mode-I condition using double-cantilever beam technique, scales linearly with the total number density of the two main networking bonds in an OSG material ( Figure 6). 28 This is because fracture of these materials is a bond breaking process and the energy dissipated during fracture scales with the number of broken networking bonds and with the energy of the bonds.…”
Section: Impact Of Network Structure and Uv Radiation On Mechanical Smentioning
confidence: 99%
“…158 UV curing technologies have enabled some reduction in dielectric permittivity (through introduction of interconnected porosity) without a significant reduction in Young's modulus. [159][160][161][162][163][164] A survey of the literature suggests that low-k ILDs with Young's moduli of 5-10 GPa have been successfully integrated into high volume manufacturing interconnect fabrication processes. 24,25,148 Similar to low-k ILDs, low-k DB materials also exhibit reduce mechanical properties relative to the PECVD a-SiN:H films originally employed.…”
Section: -122mentioning
confidence: 99%
“…The UV curing was designed to promote cross-linking of the Si-O network bonds and accelerate porogen removal resulting in the formation of nanometer size pores within the film. 11 Diffusion coefficients of linear alkanes with various chain lengths from hexane (C 6 H 14 ) to hexadecane (C 16 H 34 ), and linear fatty alcohols from hexanol (C 6 H 13 OH) to undecanol (C 11 H 23 OH), were measured using the lateral solvent diffusion technique. 9,12 To directly observe liquid penetration in the plane of the nanoporous film, the top surface of the film was first hermetically sealed with an optically transparent SiN layer.…”
mentioning
confidence: 99%